Blackwell Handbook of Social Psychology : Intraindividual Processes. - Tesser, Abraham (Blackwell Handbooks of Social Psychology., 2007)
This volume on intraindividual processes is one of a set of four handbooks in the social psychology field and covers social cognition, attitudes, and attribution theory.:.; Includes contributions by academics and other experts from around the world to ensure a truly international perspective.; Provides a comprehensive overview of classic and current research and likely future trends.; Fully referenced chapters and bibliographies allow easy access to further study.; Now available in full text online via xreferplus, the award-winning reference library on the web from xrefer. For more information.